Exoplanet Searches in the Habitable Zone with Gravitational Microlensing. Issue Volume 8:Issue S293(2012) (29th April 2014) - Zakharov, Alexander F.; Ingrosso, Gabriele; De Paolis, Francesco; Nucita, Achille A.; Strafella, Francesco; Novati, Sebastiano Calchi; Jetzer, Philippe
Abstract: There are different methods for finding exoplanets such as radial spectral shifts, astrometrical measurements, transits, timing, etc. Gravitational microlensing (including pixel-lensing) is among the most promising techniques with the potential of detecting Earth-like planets at distances about a few astronomical units from their host stars. Here we emphasize the importance of polarization measurements which can help to resolve degeneracies in theoretical models. In particular, the polarization angle could give additional information about the relative position of the lens with respect to the source.